Building Partnerships in a Global Society: The Internationalization of Education Programs - Mary Jane Harkins; Robin Neustaeter (Adult Education Research Conference, 2007)
This interactive session will explore the role of educators in a rapidly changing global society. The theoretical framework is based on a critical pedagogical approach. The focus is on discussing values, beliefs and assumptions, inherent power relationships and how these areas impact on the development of International educational partnerships.